On the Origin and Function of Human NK-like CD8+ T Cells: Charting New Territories - Fernando A. Arosa (Frontiers Research Topics, 2018)
Human CD8+ T cells expressing NK receptors and receptors found on innate immune cells, and designated as NK-like or innate CD8+ T cells, have been long considered as terminally differentiated lymphocytes responsible for tissue inflammation and destruction. However, a growing body of knowledge is unveiling that NK-like CD8+ T cells have many, sometimes contrasting, functions. The limited knowledge of the biology of this type of CD8+ T cells and the role they play within peripheral tissues and organs under homeostatic conditions has hampered our understanding of disease and therefore the possible development of disease diagnostic tools and effective immunotherapies. In this Research Topic are presented a variety of topics and views, some of them overlooked for many years, on human NK-like CD8+ T cells, which may open new and novel avenues of research to further our understanding of these polyfunctional T cells.